What's in a Name? A Grammar of Pluralism and Foundations of the Vernacular - Veeravalli, Anuradha (Religious Studies, Theology and Philosophy E-Books Online, Collection 2026., 2025)
Would it be possible to overcome the dualism of universalism and relativism that the story of the Tower of Babel portends, and modernity perpetuates? Between the dominant paradigms of the dualism of the classical and the vernacular, of universal grammar of Chomskian bio-linguistics and hermeneutic relativism of Steiner, of the ideal and ordinary language theories of Wittgensteinian socio-linguistics, this dichotomy plays itself out, again and again. Tracing the genealogy of the fundamental difference between the presuppositions of a grammar of pluralism and of universal grammar to the disagreement between Plato and Aristotle on the theory of forms, this book brings into focus the dramatic and crucial changes wrought in the liturgy of the Eucharist, in the 13th century, that consolidated Aristotelianism as the dominant regime of the Christian Church and laid the foundations of universal grammar both of the European modernity and of the modern world at large. It argues that it is the vernacular traditions however, that continually challenge this regime within different religious orthodoxies and in modernity with the reiteration and re-affirmation of the theory of the true name as the basis of a grammar of pluralism.